PENGARUH KUALITAS PRODUK DAN CITRA MEREK TERHADAP KEPUTUSAN PEMBELIAN BUNGA PAPAN “THUNDER FLORIST” DI BANDAR LAMPUNG - Beny Rachman Hakim; Aripin Ahmad (BULLET : Jurnal Multidisiplin Ilmu, 2023)
Companies must know how consumers have to choose a brand and product quality in making purchases, well-known brands and good product quality make it easier for consumers to make decisions. For this reason, the problem is whether product quality and brand image affect the purchasing decision of Thunder Florist Flower Boards in Bandar Lampung. The aim of this research is to find out whether product quality and brand image affect purchasing decisions. The analysis used in this study is multiple linear regression analysis. The hypothesis proposed is the effect of product quality and brand image on purchasing decisions of Thunder Florist flower boards in Bandar Lampung. The significance value of F count is 0.000 which is smaller than the research Alpha of 5%, so Ho is rejected and Ha is accepted. Statistically, the overall independent variables (product quality and brand image) have a positive and significant effect on the decision to buy a Thunder Florist flower board in Bandar Lampung. The significance value of t calculated on the Product Quality variable is 0.000, which is less than the Alpha in the research of 5%. This means that Product Quality has a positive and significant influence on the Purchase Decision of Thunder Florist Flower Boards in Bandar Lampung. The significance value of t is calculated on the brand image variable of 0.000 which is smaller than the research Alpha of 5%. This means that Brand Image has a positive and significant influence on the Purchase Decision of Thunder Florist Flower Boards in Bandar Lampung.